Do Numbers Exist?: A Debate About Abstract Objects - Peter Van Inwagen, William Lane Craig (New York Routledge, 2024)
Office of Academic Affairs
MIR No: 170
Order Date: 2024-08-29
Order No: CU/OPEX/LIBRARY/30/2024-25
Received Date: 2024-09-25
Keywords: Philosophical Logic